ESTIMATION OF HEIGHT USING HEAD CIRCUMFERENCE OF MEDICAL STUDENTS IN PESHAWAR, PAKISTAN - Shahabuddin; Haq, Anwar Ul; Khushbakht, Urooj; Naheed Siddiqui (Journal of Postgraduate Medical Institute, 2024)
Objectives: To ascertain whether head circumference can be utilized to estimate stature in students from the medical college in Peshawar. Methodology: In this study, we aimed to investigate the relationship between height and head circumference in a cohort of first-year students from a public medical college. The sample comprised 140 participants, evenly split between 70 males and 70 females, with ages ranging from 18 to 20 years. For height measurement a stadiometer was used, and a measuring tape was used to gauge head circumference. Regression equation was used to analyze the data for estimating height from circumference of head. Results: In this study, the average height of males was determined to be 174.860 cm with a standard deviation of 5.745 cm, while the average head circumference was 54.926 cm with a standard deviation of 1.590 cm. Conversely, females exhibited an average height of 160.842 cm with a standard deviation of 5.540 cm, and an average head circumference of 53.245 cm with a standard deviation of 1.286 cm. Conclusion: In conclusion, our study underscores the significance of head circumference as a reliable indicator for assessing stature in both males and females. The observed significant relationship between head circumference and height in both sexes suggests that head circumference can serve as a robust parameter for estimating height. These findings contribute to the field of anthropometry, providing practical implications for height estimation based on head circumference, and may have relevance in diverse contexts, such as clinical assessments or population studies.